Critical Success Factors Influencing Adoption of Internet Technology by MSC & Non-MSC Companies - Yew King, lloyd Tam (Universiti Putra Malaysia Press, 2002)
The Internet is transforming the way in which business strategies are formulated in the corporate world. Indeed, it is proving to be the most effective and influential strategic tool of the century by connecting thousands of companies and millions of people every minute. This paper highlights the salient factors influencing the adoption of Internet technology by MSC and 10n-MSC companies. Five organisational and two marketplace factors were used in this study. The final analysis confirmed that MSC and Non-MSC companies were influenced by six factors - perceived direct benefits, organisational compatibility, technical complexity, trading partner pressure, organisational support, and perceived direct benefits. All of the factors above except for technical complexity proved that Non-MSC companies were more affected by these factors than MSCn companies. Another factor, competitive pressure, was not an influential factor.